Cryopreservation of Platelet Concentrates Under Moderately Low Temperatures (–70…–80°C) with Preservatives Based on Combination of Cryoprotectants - Korobkova, Anna V.; Kompaniets, Antonina M. (Problems of Cryobiology and Cryomedicine, 2015)
N/A